Pengaruh Lingkungan Bermain terhadap Kematangan Sosial Emosional Anak Usia 3–5 Tahun di Tempat Penitipan Anak - Sri Yulita Sa'ban; Lisnawaty Atuna; Ribbi Aulia Salsabila; Siti Alizah A. Sua (Institut Nalanda, 2025)
This study aims to examine the influence of play environment on the social-emotional maturity of children aged 3–5 years in childcare centers. The research employed a quantitative survey method involving 60 children as samples. Data were collected through questionnaires and observations, then analyzed using correlation and simple linear regression tests. The results indicate that the play environment has a positive and significant effect on children’s social-emotional maturity. A safe, supportive play environment equipped with adequate facilities and responsive caregivers helps children develop social interaction skills, emotional regulation, and empathy. These findings emphasize the importance of improving the quality of play environments in childcare centers to support early childhood social-emotional development. The practical implication of this study is the need for optimal management of play environments and caregiver training as part of efforts to enhance early childhood education quality.